Social factors, health care inequities and vaccination - Kronenfeld, Jennie Jacobs (Emerald Publishing Limited, 2023)
This volume of Research in the Sociology of Health Care analyses a variety of important social factors and their relationship to health and health care inequities in both the United States and the rest of the world. With distinct sections for vaccination and other related topics, the chapters unveil the health care inequities that exist across a broad range of scenarios such as residential segregation, rurality, caregiving during COVID-19, the effects of stress on patients of color with chronic illnesses, cochlear implants in children, community health centers and viral load testing. Employing a sociological and broader social sciences approach, Social Factors, Health Care Inequities and Vaccination draws on a variety of contexts, including the COVID-19 pandemic, to explore wider trends in healthcare and the impact they may have on historically disadvantaged communities.
Keywords: Social medicine.; Health services accessibility.; Medical care.; Medical policy.; Public health -- Social aspects.; Social Science -- Disease & Health Issues.; Medical sociology.; elektronické knihy; electronic books